Education of 3R (Reduce, Reuse, Recycle) Waste Management For Students Of SD Negeri Nomor 4 Tiga Village using Wall Magazine: Edukasi Metode Pengolahan Sampah 3R (Reduce, Reuse, Recycle) Kepada Siswa SD Negeri Nomor 4 Desa Tiga dengan Media Majalah Dinding - Nurhadi, Wayan Sandhi Putra; Permana, Gusi Putu Lestara; Darma, I Made Wirya; Sutama, I Wayan; Gorda, AAA. Ngurah Sri Rahayu; Martini, I. A. Oka (Yayasan Ahmar Cendekia Indonesia, 2023)
Community service has been carried out in Tiga Village, Susut District, Bangli Regency, Bali Province. This community service activity was carried out for 27 days, starting from January 16 to February 11, 2023. Desa Tiga traditionally has one unit and is summarized in Gebong Satak Tiga Buungan which consists of 9 Pakraman villages. In Tiga Village, there are several potentials to be used as work programs, namely the agricultural sector, the livestock sector, tourism objects, teaching and education. This potential can help the main objective of implementing community service, namely to improve the quality of human resources in improving and developing the quality of the village. This community service begins with an assessment process to find out the village's potential as a means of implementing community service. The implementation of the community service program is carried out in a balanced manner starting with planning, maturation and implementation of the work program, the potential that researchers choose here is how to sort waste in the 3R way through education with wall magazine media. Abstrak Pengabdian kepada masyarakat telah dilaksanakan di desa Tiga, kecamatan susut, kabupaten Bangli, provinsi Bali. Kegiatan pengabdian masyarakat ini Dilaksanakan selana 27 hari, yang dimulai pada tanggal 16 januari sampai 11 februari 2023. Desa tiga secara adat istiadat memiliki satu kesatuan dan terangkum didalam gebong satak tiga buungan yang terdiri dari 9 desa pakraman. Di Desa Tiga ini terdapat beberapa potensi untuk dijadikan program kerja yaitu diantaranya sektor pertanian, sektor perternakan, objek wisata, mengajar dan edukasi. Potensi tersebut dapat membantu tujuan utama pelaksanaan pengabdian masyarakat yaitu untuk meningkatkan kualitas sumber daya manusia dalam meningkatkan dan mengembangkan kualitas desa tersebut. Pengabdian masyarakat ini diawali dengan proses penjajakan untuk mengetahui potensi desa yang menjadi sarana dalam pelaksanaan pengabdian masyarakat. Pelaksanaan program pengabdian masyarakat dilakukan secara seimbang diawali dengan perencanaan, pematangan serta pelaksanaan program kerja tersebut, potensi yang peneliti pilih disini adalah bagaimana memilah sampah dengan cara 3R melalui edukasi dengan media majalah dinding